Preferences in Information Processing: Understanding Suicidal Thoughts and Behaviors among Active Duty Military Service Members. Issue 1 (2nd January 2022) - Cramer, Robert J.; Franks, Michael; Cunningham, Craig A.; Bryan, Craig J.
Abstract: The present study examined Preferences in Information Processing (PIP), an emerging model of understanding suicidal thoughts and behaviors (STBs), in a clinical military sample for the first time. Constructs of need for affect (NFA; i.e., extent to which one engages or avoids emotional content) and need for cognition (NFC; i.e., extent of preference for and enjoyment of cognitive effort) are central individual differences of the PIP model hypothesized to be associated with STBs. Data ( n = 200 active duty personnel) were drawn from medical records and self-report questionnaires from two outpatient treatment settings in a military hospital. Primary findings include: (1) moderate positive bivariate associations of NFA avoidance with mental health symptoms and lifetime STBs; (2) consistent patterns in which NFA approach buffers the negative associations of depression with life STBs, clinical suicide risk, perceived burdensomeness and thwarted belonging. Recommendations are offered for military suicide prevention, and future suicide theory testing.